An abnormally deep palmar muscle: a case description - Goloborod'ko, Sergey; Vasilinets, Mykhaylo (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
A rare case of an abnormally deep palmar muscle is described. The muscle was found out in a female patient with the clinical picture of carpal tunnel syndrome. In the process of an operation, a thickened median nerve was revealed; a tendon, tightly connected to the above nerve with their common fascial coat, passed along the radial surface of the nerve. Separation of the tendon from the nerve and mesoepineurolysis were followed by transposition of the median nerve outside the carpal tunnel.